Forced Religious Conversions in Pakistan - Haji Sanwan Alias Fayaz Hyder; Dr. Tansif Ur Rehman; Atta Muhammad; Prof. Dr. Sobia Anees Shahzad; Adnan Zawar; Mehmood Ahmed Usmani; Syed Adeel Ali Bukhari (Al-Mahdi Research Journal (MRJ), 2024)
This research critically examines the alarming phenomenon of forced conversions among religious minorities in Pakistan, with a particular focus on the Sindhi Hindu community. It investigates the intricate sociocultural, economic, and gender-based vulnerabilities that facilitate these coercive practices, shedding light on the influential role of religious leaders and societal pressures. The study analyzes the existing legal framework in Pakistan, identifying significant gaps that enable forced conversions to persist despite constitutional guarantees of religious freedom. Additionally, it evaluates the formidable challenges law enforcement and the judiciary face in delivering justice to victims. The research further explores the profound psychological and social effects of forced conversions on victims and their families, highlighting the disproportionate targeting of women and girls. By proposing comprehensive legal and policy reforms, this study aims to fortify protections for religious minorities and enhance Pakistan’s commitment to human rights, contributing to a deeper understanding of forced conversions and advocating for accountability and reform within the legal system.